The function \( f(x)=7 x+5 \) is one-to-one. a. Find an equation for \( f^{-1} \), the inverse function. b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \).
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To find the inverse function \( f^{-1} \) of the equation \( f(x) = 7x + 5 \), we start by setting \( y = f(x) \): \[ y = 7x + 5. \] Next, we solve for \( x \) in terms of \( y \): \[ y - 5 = 7x \quad \Rightarrow \quad x = \frac{y - 5}{7}. \] Thus, the inverse function is \[ f^{-1}(x) = \frac{x - 5}{7}. \] Now, we'll verify this by checking \( f(f^{-1}(x)) \) and \( f^{-1}(f(x)) \). 1. **Verifying \( f(f^{-1}(x)) = x \)**: \[ f(f^{-1}(x)) = f\left(\frac{x - 5}{7}\right) = 7\left(\frac{x - 5}{7}\right) + 5 = x - 5 + 5 = x. \] 2. **Verifying \( f^{-1}(f(x)) = x \)**: \[ f^{-1}(f(x)) = f^{-1}(7x + 5) = \frac{(7x + 5) - 5}{7} = \frac{7x}{7} = x. \] Since both verifications hold true, the inverse function \( f^{-1}(x) = \frac{x - 5}{7} \) is confirmed correct!